Islamic Educational Transformation through Inmate Social Interaction at Palu Correctional Facility Class II A, Central Sulawesi - Yusra; Markarma, A (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The rehabilitation system adopted by the correctional facility is based on Pancasila. All incarcerated men are rehabilitated there with the goal to make them repent, be law-abiding citizens, and uphold moral values. The correctional facility comes as a rehabilitation place to improve social interaction so that inmates can be received by their social environment once they are released from prison. At this point, the researcher focuses on Islamic educational transformation through the inmate social interaction training program at Palu correctional facility class II A. This research uses a descriptive quantitative design with a social legal approach to observe patterns of inmate social interaction. The result of research points out that Islamic educational transformation which is packed into rehabilitation programs and correctional educational activities is remarkably emphasized in inmate social interaction. In this case, Islamic educational transformation applied in Palu correctional facility class II A is defined as ultimum remidium, correctional activities emphasizing on process-based approach. The rehabilitation process given to inmates is able to improve insight and awareness of ethical and moral values in their social interaction. Therefore, when returning to the society they can be accepted by the social environment as good responsible people.